2021
DOI: 10.3389/fneur.2021.698599
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed Trajectory During the Six-Minute Walk Test in Multiple Sclerosis: A Measure of Walking Endurance

Abstract: Background: The six-minute walk (6MW) test is a validated assessment method in Multiple Sclerosis (MS) research. While the total distance covered during six minutes (6MWTD) is often used as the standard measurement of gait capacity (i.e., the maximum distance one can achieve), we hypothesize that endurance (i.e., ability to maintain speed over a prolonged time) can be inferred by the gait speed trajectory (GST) during the 6MW test (6MWGST).Objective: To characterize group differences in 6MWGST between MS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…On the other hand, in healthy people, we observed a rebound pattern as already described in the literature [ 12 , 25 , 28 ], but we highlighted here that the ST variables’ changes between 6MWT intervals were negligible, i.e., healthy people could maintain their rhythm throughout the 6MWT. Healthy people seemed to conserve abilities to maintain velocity by modulating their two components of velocity: cadence and stride length ( Table 2 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, in healthy people, we observed a rebound pattern as already described in the literature [ 12 , 25 , 28 ], but we highlighted here that the ST variables’ changes between 6MWT intervals were negligible, i.e., healthy people could maintain their rhythm throughout the 6MWT. Healthy people seemed to conserve abilities to maintain velocity by modulating their two components of velocity: cadence and stride length ( Table 2 ).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, we observed that PwMS had a different ST walking pattern compared to healthy people (e.g., PwMS had a “constant decline” pattern, i.e., a monotonous decrease in velocity was observed during the 6MWT, whereas a “rebound” pattern was found in the healthy group). These results corroborate and complete previous studies in which only walking velocity was analyzed in PwMS [ 12 , 28 ]. Because the first reliability step was checked and to complementarily confirm the clinical pertinence of our previous results, this study aimed to focus on the analysis of the difference between the ST walking pattern of PwMS and healthy people during specific intervals in the 6MWT.…”
Section: Introductionsupporting
confidence: 91%
“…Patients with MS walk slower and their speed declines faster over time than that of healthy controls ( 59 , 60 ). In contrast, some, although not all studies that assessed isolated muscle fatigability did demonstrate significant differences in force decline during voluntary contractions between MS patients and healthy controls ( 52 , 57 , 61 ).…”
Section: Current Concepts Of Motor Fatigue In Ms: Definitions Assessm...mentioning
confidence: 99%
“… 5 It has been previously reported that quadriceps dysfunction results in a series of consequences such as aggravated dyspnea symptoms, reduced muscular capacity and endurance. 6 , 7 Various clinical features are commonly used to evaluate the physical performance of a given patient, including the Six-Minute Walk Test (6MWT) 8 to assess muscular endurance, the Five-Repetition Sit-to-Stand Test (5STS) 9 to reflect the muscle strength, the COPD Assessment Test (CAT) 10 and the modified British Medical Research Council score (mMRC) to evaluate the patient’s overall health and dyspnea. Although the translated CAT and mMRC questionnaires are simple and easy to fill in, there are still subjective differences in the understanding of breathing difficulties and physical condition between different patients.…”
Section: Introductionmentioning
confidence: 99%